Impact of isotype on the mechanism of action of agonist anti-OX40 antibodies in cancer: implications for therapeutic combinations - Junping Jing; Laura Bover; C Ian Mockridge; Kerry L Cox; Mark S Cragg; Tatyana Inzhelevskaya; Chris A Penfold; Vikki English; Jane E Willoughby; Hong Shi; Peter J Morley; Heather Jackson; et al. (Journal for ImmunoTherapy of Cancer)
Background OX40 has been widely studied as a target for immunotherapy with agonist antibodies taken forward into clinical trials for cancer where they are yet to show substantial efficacy. Here, we investigated potential mechanisms of action of anti-mouse (m) OX40 and anti-human (h) OX40 antibodies, including a clinically relevant monoclonal antibody (mAb) (GSK3174998) and evaluated how isotype can alter those mechanisms with the aim to develop improved antibodies for use in rational combination treatments for cancer.Methods Anti-mOX40 and anti-hOX40 mAbs were evaluated in a number of in vivo models, including an OT-I adoptive transfer immunization model in hOX40 knock-in (KI) mice and syngeneic tumor models. The impact of FcγR engagement was evaluated in hOX40 KI mice deficient for Fc gamma receptors (FcγR). Additionally, combination studies using anti-mouse programmed cell death protein-1 (mPD-1) were assessed. In vitro experiments using peripheral blood mononuclear cells (PBMCs) examining possible anti-hOX40 mAb mechanisms of action were also performed.Results Isotype variants of the clinically relevant mAb GSK3174998 showed immunomodulatory effects that differed in mechanism; mIgG1 mediated direct T-cell agonism while mIgG2a acted indirectly, likely through depletion of regulatory T cells (Tregs) via activating FcγRs. In both the OT-I and EG.7-OVA models, hIgG1 was the most effective human isotype, capable of acting both directly and through Treg depletion. The anti-hOX40 hIgG1 synergized with anti-mPD-1 to improve therapeutic outcomes in the EG.7-OVA model. Finally, in vitro assays with human peripheral blood mononuclear cells (hPBMCs), anti-hOX40 hIgG1 also showed the potential for T-cell stimulation and Treg depletion.Conclusions These findings underline the importance of understanding the role of isotype in the mechanism of action of therapeutic mAbs. As an hIgG1, the anti-hOX40 mAb can elicit multiple mechanisms of action that could aid or hinder therapeutic outcomes, dependent on the microenvironment. This should be considered when designing potential combinatorial partners and their FcγR requirements to achieve maximal benefit and improvement of patient outcomes.